2017
DOI: 10.4103/jmh.jmh_46_17
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial status and economic dependence for healthcare and nonhealthcare among elderly population in rural coastal Karnataka

Abstract: Introduction:The elderly who will constitute 10% of the Indian population by 2021 face problems such as deteriorating healthcare status, loneliness, and economic constraints among others. All these factors together may affect the psychosocial status of the elderly and their health-seeking behavior. With this background, the current study tried to evaluate the psychosocial status, economic dependence for health and nonhealth expenses and awareness regarding geriatric welfare services (GWS) among elderly patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
3
8
0
Order By: Relevance
“…[22] Lack of income or financial dependence on another may force elderly people to forego treatment altogether, which may cause further deterioration of their quality of life. [23] The results of present and other studies proves that financial dependency is a very crucial factor determining health and well-being at old age. [222324]…”
Section: Discussionsupporting
confidence: 58%
“…[22] Lack of income or financial dependence on another may force elderly people to forego treatment altogether, which may cause further deterioration of their quality of life. [23] The results of present and other studies proves that financial dependency is a very crucial factor determining health and well-being at old age. [222324]…”
Section: Discussionsupporting
confidence: 58%
“…10 However, many studies have reported that the elderly advice was honoured in the family. 22,23 Financial security is another major challenge for the aging population in India. The elderly often do not have financial protection such as sufficient pensions and other forms of social security in India.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation, loneliness, sense of neglect and boredom are the common complaints of the older adults. All these factors influence the psychosocial status of the older adults [32,33], leading to differences of the willingness to use healthcare services.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%